1979
DOI: 10.1007/bf00388770
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of 1-triacontanol as a plant growth stimulator and inhibition of its effect by other long-chain compounds

Abstract: The effect of several analogs of 1-triacontanol (TRIA), differing in C-chain length (16-32), the position of the hydroxyl group and the terminal functional group, were tested alone and in combination with TRIA on the growth of rice (Oryza sativa L.), maize (Zea mays L.) and tomato (Lycopersicon esculentum Mill.) seedlings. Applied alone, none of the compounds caused an increase in growth; thus, chain length (30 C) and presence and position (terminal) of the hydroxyl group appear to be specific for the growth-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…seedlings, within 10 min of a foliar application of 1 .0 tg/L [15] . Octacosanol (OCTA), a n-C 28 alcohol applied to either rice roots or shoots 1 min prior to TRIA treatment of the opposite organ of the seedling inhibits this response [7,15] . TRIA quickly elicits a new growth substance (TRIM) that moves rapidly (within 1 min) throughout the plant resulting in stimulation of growth (dry weight increase) and water uptake [16] .…”
Section: Introductionmentioning
confidence: 99%
“…seedlings, within 10 min of a foliar application of 1 .0 tg/L [15] . Octacosanol (OCTA), a n-C 28 alcohol applied to either rice roots or shoots 1 min prior to TRIA treatment of the opposite organ of the seedling inhibits this response [7,15] . TRIA quickly elicits a new growth substance (TRIM) that moves rapidly (within 1 min) throughout the plant resulting in stimulation of growth (dry weight increase) and water uptake [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al. (11) demonstrated that a chain length of 30 carbons with a terminal hydroxyl group was specific for TRIA's growthpromoting activity. Tests of the growth-promoting activity of TRIA analogs, varying in chain length from 16 to 32 carbons, proved negative.…”
mentioning
confidence: 99%
“…Tests of the growth-promoting activity of TRIA analogs, varying in chain length from 16 to 32 carbons, proved negative. In fact, these compounds resulted in inhibition of the TRIA response when applied simultaneously (11). Thus, the primary alcohols, octocosanol (28-C) and tetracosanol (24-C), are excellent inhibitors of the TRIA response at equimolar rates.…”
mentioning
confidence: 99%
“…6) Octacosanol Inhibition. Octacosanol, a 28-carbon straightchain primary alcohol, which inhibits the effects of TRIA on higher plants ( 13), also inhibited the increase in photosynthetic CO2 assimilation in TRIA-treated Chlamydomonas cells (Table IV). Octacosanol alone had no effect on photosynthetic CO2 assimilation; therefore, the effect ofTRIA on this process appears to be specific for TRIA.…”
Section: Methodsmentioning
confidence: 96%